2009
DOI: 10.1002/chin.200952231
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A Comparison of Several Modern Alkylating Agents

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The fact that DMAD and DEAD reacted showed that the displacement step could have S N 2 character. 17 EXPERIMENTAL Microwave irradiation was performed with a Milestone ETHOS 1600 microwave oven. The chemicals were purchased from Fluka and used without further purification.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that DMAD and DEAD reacted showed that the displacement step could have S N 2 character. 17 EXPERIMENTAL Microwave irradiation was performed with a Milestone ETHOS 1600 microwave oven. The chemicals were purchased from Fluka and used without further purification.…”
Section: Resultsmentioning
confidence: 99%
“…MeOTf and its perfluoro analogs such as methyl nona‐fluorobutyl‐1‐sulfonate (MeONf) are powerful reagents for methylation and are more reactive by a factor of approximately 10 4 than methyl iodide and Me 2 SO 4 . In many cases, they are used as N‐, O‐, or S‐methylation reagents under basic conditions. The literature on the uses of these methyl sulfonates as methylation reagents are very profuse .…”
Section: Methylation By Using Conventional Reagentsmentioning
confidence: 99%
“…Several recent reviews on methylation focused on different aspects, for example, using dimethyl carbonate as the methylation reagent, carbon dioxide for transition‐metal‐free catalysis for N‐methylation, peroxides, other radical sources to generate the methyl radical, metal‐catalyzed methylation, decarboxylative methylation, the use of methanol in Mitsunobu reactions, hydrogen borrowing strategies, nickel‐catalyzed reductive couplings of alkyl electrophiles, cross‐coupling methods for C‐methylation, and photoredox catalysis . In 2009, Lamoureux and Agüero published a review comparing several alkylating agents . Among other reviews, the one by Aurelio and Hughes is noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Methylethers are considered as good oxygenated molecules due to their capacity to reduce CO emission, and to enhance gasoline combustion increasing octane numbers. They also exhibit excellent properties as solvents for extractions, and are used in several applications such as coatings, inks, paints, cleaning agents and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%